(untitled) (Journal of Pharma Insights and Research, 2024)
Pancreatitis is an inflammatory condition of the pancreas, which serves as both an exocrine organ for food digestion and an endocrine organ for regulating blood sugar levels. The disease is typically accompanied by moderate to severe pain, necessitating the use of analgesics for effective pain management. This research aims to evaluate and compare the efficacy of various analgesics in alleviating pain associated with pancreatitis. Ultimately, the study aims to gain a comprehensive understanding of the outcomes resulting from different pain management strategies in individuals with pancreatitis. A comparative research study was conducted at Basaveshwara General Hospital in Kalaburagi, Karnataka, over a period of six months, involving 100 patients selected from both general and university hospital settings. The findings revealed that out of 100 patients, 76% were males, and 24% were females affected by pancreatitis. Throughout the study, a total of 164 analgesics were administered, with the highest frequency of potent analgesics prescribed within the age group of 5-46 years. Notably, Nalbuphine emerged as the most commonly prescribed analgesic via the parenteral route, constituting 39% of the total prescriptions. For cases with mild to moderate pain, Paracetamol was the preferred analgesic, accounting for 35.3% of the prescriptions. This research investigates the variations in analgesic prescriptions for pancreatitis pain management, tailoring prescriptions to the severity of pain, with non-opioid analgesics recommended for mild to moderate pain levels